Relationship between Knowledge, Attitudes, and Actions in Waste Management with Community Participation in the Waste Bank Program in Serang Regency - Sita Oktafiani Eka Putri; Linda Lestari; Ismarina; Rita Ramayulis (Health and Technology Journal (HTechJ), 2024)
A waste bank is a place for sorting and collecting waste that can be recycled or reused, which has economic value. The waste bank mechanism consists of sorting household waste banks, depositing waste to banks, weighing waste, recording, and transporting collected waste. This study aimed to determine the relationship between knowledge, attitudes, and actions regarding waste management in Lebakwana Village, Kramatwatu District, during research time in 2022, with a sample of 57 respondents. Data collection techniques used primary and secondary data; the data analyses were univariate and bivariate analyses. Based on the results of knowledge research with community participation in the waste bank program through Chi-square, the p-value is (1,000) > (0.05). Therefore, the proposed hypothesis (Ha) is not accepted. There is no significant relationship between knowledge and community participation in the waste bank program in Serang City.